Role of nurses and nurse practitioners in the recognition, diagnosis, and management of neurogenic orthostatic hypotension: a narrative review - Biswas D; Karabin B; Turner D (International Journal of General Medicine, 2019)
Debashis Biswas,1 Beverly Karabin,2 Debra Turner3 1Neurology, Baptist Memorial Hospital-Memphis, Memphis, TN, USA; 2Cardiovascular Medicine, University of Toledo, Toledo, OH, USA; 3Autonomic Services, Semmes Murphey Clinic, Memphis, TN, USA Abstract: Neurogenic orthostatic hypotension (nOH) is a sustained reduction in blood pressure (BP) upon standing that is caused by autonomic dysfunction and is common among patients with a variety of neurodegenerative disorders (eg, Parkinson’s disease, multiple system atrophy, pure autonomic failure). A systolic BP drop of ≥20 mmHg (or ≥10 mmHg diastolic) upon standing with little or no compensatory increase in heart rate is consistent with nOH. Symptoms of nOH include light-headedness, dizziness, presyncope, and syncope; these symptoms can severely impact patients’ activities of daily living and increase the likelihood of potentially dangerous falls. Because of their patient contact, nurses and nurse practitioners can play a key role in identifying and evaluating patients at risk for nOH. It is advisable to screen for nOH in patients presenting with one or more of the following characteristics: those who have disorders associated with autonomic failure, those with episodes of falls or syncope, those with symptoms upon standing, those who are elderly or frail, or those taking multiple medications. Initial evaluations should include questions about postural symptoms and measurement of orthostatic BP and heart rate. A review of medications for potential agents that can have hypotensive effects should be performed before initiating treatment. Treatment for nOH may include non-pharmacologic measures and pharmacologic therapy. Droxidopa and midodrine are approved by the US Food and Drug Administration for the treatment of symptomatic nOH and symptomatic OH, respectively. nOH is associated with the coexistence of supine hypertension, and the two disorders must be carefully managed. In conclusion, timely screening and diagnosis of patients with nOH can streamline the path to disease management and treatment, potentially improving patient outcomes. Keywords: blood pressure, autonomic nervous system, screening, diagnosis